Oxford handbook of food ethics - Anne Barnhill; Budolfson, Mark; Doggett, Tyler (New York Oxford University Press, 2018)
Academic food ethics incorporates work from philosophy but also anthropology, economics, the environmental sciences and other natural sciences, geography, law, and sociology. Scholars from these fields have been producing work for decades on the food system, and on ethical, social, and policy issues connected to the food system. Yet in the last several years, there has been a notable increase in philosophical work on these issues-work that draws on multimillionaires within practical ethics, normative ethics and political philosophy. This handbook provides a sample of that philosophical work across multiple areas of food ethics: conventional agriculture and alternatives to it; animals; consumption; food justice; food politics; food workers; and, food andidentity. Table of contents : - 1. Introduction Anne Barnhill, Mark Budolfson, Tyler Doggett Part One: Conventional Agriculture and Alternatives2. Sustainable Agriculture, Environmental Philosophy, and the Ethics of Food Clark Wolf3. Farming, the Virtues and Agrarian Philosophy Paul Thompson4. Food, the Environment, and Global Justice Mark Budolfson5. Genetically-Modified food: Fostering Better Dialogue About What Counts as 'Good' Food Rachel Ankeny and Heather Bray6. Local Food Movements: Differing Conceptions of Food, People, and Change Samantha Noll and Ian WerkheisePart Two: Animals7. Concerning Cattle: Behavioral and Neuroscientific Evidence for Pain, Desire, and Self-Consciousness Gary Comstock8. The New Hunter and Local Food Charles List9. Ethics for Fish Eliot Michaelson and Andrew ReisnerPart Three: ConsumptioAcademic food ethics incorporates work from philosophy but also anthropology, economics, the environmental sciences and other natural sciences, geography, law, and sociology. Scholars from these fields have been producing work for decades on the food system, and on ethical, social, and policy issues connected to the food system. Yet in the last several years, there has been a notable increase in philosophical work on these issues-work that draws on multipleliteratures within practical ethics, normative ethics and political philosophy. This handbook provides a sample of that philosophical work across multiple areas of food ethics: conventional agriculture and alternatives to it; animals; consumption; food justice; food politics; food workers; and, food andidentity. Table of contents : - 1. IntroductionAnne Barnhill, Mark Budolfson, Tyler Doggett Part One: Conventional Agriculture and Alternatives2. Sustainable Agriculture, Environmental Philosophy, and the Ethics of Food Clark Wolf3. Farming, the Virtues and Agrarian Philosophy Paul Thompson4. Food, the Environment, and Global Justice Mark Budolfson5. Genetically-Modified food: Fostering Better Dialogue About What Counts as 'Good' Food Rachel Ankeny and Heather Bray6. Local Food Movements: Differing Conceptions of Food, People, and Change Samantha Noll and Ian WerkheisePart Two: Animals7. Concerning Cattle: Behavioral and Neuroscientific Evidence for Pain, Desire, and Self-Consciousness Gary Comstock8. The New Hunter and Local Food Charles List9. Ethics for Fish Eliot Michaelson and Andrew ReisnerPart Three: Consumption10. The Ethical Basis for Veganism Tristram McPherson11. Arguments for Consuming Animal Products Bob Fischer12. Consumer Choice and Collective Impact Julia Nefsky13. Religion, Fasting, Efficacy, Hope Andrew Chignell14. The Clean Plate Club? Food Waste and Individual Responsibility Erich and Jaclyn Hatala MatthesPart Four: Food Justice and Social Justice 15. Racial Imperialism and Food Traditions Lee McBride16. Food Sovereignty, Justice and Indigenous Peoples: An Essay on Settler Colonialism and Collective Continuance Kyle Powys Whyte17. Food, Fairness, and Global Markets Madison Powers18. Multi-Issue Food Activism: The Ethics of Pursuing Unity, Solidarity, and Mutual Understanding across Food Movements Jeff SeboPart Five: Ethics and Politics of Food Policy19. Public Justification and the Politics of Agriculture Danny Shahar20. Paternalism, Food, and Personal Freedom Sarah Conly21. Deceptive Advertising and Taking Responsibility for Others Seana Shiffrin22. Food Labor Ethics Tyler Doggett and Seth Holmes23. The Moral Burdens of Temporary Farmwork Sabine TsurudaPart Six: Gender, Body Image and "Healthy" Eating24. Orthorexia: Eat Y'Self Fitter: Orthorexia, Health, and Gender Christina van Dyke25. Food Insecurity: Dieting as Ideology, as Oppression, and as Privilege Tracy Isaacs26. Shame, Seduction, and Character in Food Messaging Rebecca Kukla27. Obesity and Responsibility Beth DixonPart Seven: Food and Social Identities, Cultural Practices and Values28. I Eat, Therefore I Am: Disgust and the Intersection of Food and Identity Dan Kelly and Nicolae Morar29. Morality and Aesthetics of Food Sam Liao and Aaron Meskin30. Food Choices & Moral Character Kate Nolfi31. The Etiquette of Eating Karen Stohr32. The Ethics of Being a Foodie Susan WolfPart Eight: History of Philosophy and Food Ethics33. Who You Are Is What You Eat: Food in Ancient Thought Katja Vogt34. Food Ethics in the Middle Ages Henrik Lagerlund35. You Are What You Eat, But Should You Eat What You Are? Modern Philosophical Dietetics John Grey and Aaron Garrettn10. The Ethical Basis for Veganism Tristram McPherson11. Arguments for Consuming Animal Products Bob Fischer12. Consumer Choice and Collective Impact Julia Nefsky13. Religion, Fasting, Efficacy, Hope Andrew Chignell14. The Clean Plate Club? Food Waste and Individual Responsibility Erich and Jaclyn Hatala MatthesPart Four: Food Justice and Social Justice 15. Racial Imperialism and Food Traditions Lee McBride16. Food Sovereignty, Justice and Indigenous Peoples: An Essay on Settler Colonialism and Collective Continuance Kyle Powys Whyte17. Food, Fairness, and Global Markets Madison Powers18. Multi-Issue Food Activism: The Ethics of Pursuing Unity, Solidarity, and Mutual Understanding across Food Movements Jeff SeboPart Five: Ethics and Politics of Food Policy19. Public Justification and the Politics of Agriculture Danny Shahar20. Paternalism, Food, and Personal Freedom Sarah Conly21. Deceptive Advertising and Taking Responsibility for Others Seana Shiffrin22. Food Labor Ethics Tyler Doggett and Seth Holmes23. The Moral Burdens of Temporary Farmwork Sabine TsurudaPart Six: Gender, Body Image and "Healthy" Eating24. Orthorexia: Eat Y'Self Fitter: Orthorexia, Health, and Gender Christina van Dyke25. Food Insecurity: Dieting as Ideology, as Oppression, and as Privilege Tracy Isaacs26. Shame, Seduction, and Character in Food Messaging Rebecca Kukla27. Obesity and Responsibility Beth DixonPart Seven: Food and Social Identities, Cultural Practices and Values28. I Eat, Therefore I Am: Disgust and the Intersection of Food and Identity Dan Kelly and Nicolae Morar29. Morality and Aesthetics of Food Sam Liao and Aaron Meskin30. Food Choices & Moral Character Kate Nolfi31. The Etiquette of Eating Karen Stohr32. The Ethics of Being a Foodie Susan WolfPart Eight: History of Philosophy and Food Ethics33. Who You Are Is What You Eat: Food in Ancient Thought Katja Vogt34. Food Ethics in the Middle Ages Henrik Lagerlund35. You Are What You Eat, But Should You Eat What You Are? Modern Philosophical Dietetics John Grey and Aaron Garrett
Keywords: Food